To study the correlation of serum vitamin D3 level and degree of control in asthmatic children on inhaled corticosteroids - Ramakrishnan, Nithiyanantham; Sivathanu, Shobhana; Josephine, Andrea; Sampath, Sowmya (Indian Journal of Child Health, 2016)
Background: Childhood asthma is more of a syndrome with complex interplay of gene-environment-lifestyle factors not only for its causation but also for its control with pharmacological therapy. Vitamin D deficiency has been implicated as a risk factor for the causation of asthma and for its poor control in children. Objective: To study the correlation of serum vitamin D3 level and degree of control in asthmatic children on inhaled corticosteroids. Methods: It was an observational study conducted in the pediatric asthma clinic of a Government Medical College Hospital. The study population consisted of 75 asthmatic children aged 5-15 years. Children with persistent asthma on inhaled corticosteroids were classified into three groups based on global initiative for asthma guidelines. Serum vitamin D levels were measured in all the three groups and an attempt was made to find a correlation between asthma control and vitamin D levels. Results: Among the study group, 33% belonged to controlled group, 35% to uncontrolled group and 33% to partly controlled group. 71% of the asthmatic children were found to be either vitamin D deficient/insufficient. Around 81% of uncontrolled asthmatic children were vitamin D deficient, whereas only 12% of well controlled asthmatics had documented vitamin D deficiency. Among the children in controlled group, the majority (72%) were found to have normal vitamin D status. On comparison of asthma control between the groups, there was a statistically significant difference in vitamin D levels between controlled and uncontrolled group (p<0.001). The majority of children in the uncontrolled group constituted girls (69.2%) and 94% of them were vitamin D deficient. Conclusion: Vitamin D deficiency/insufficiency is widely prevalent in children with persistent asthma and lower levels of vitamin D are associated with poor asthma control. Girls formed a greater percentage of uncontrolled group and majority of them were vitamin D deficient.